1981
DOI: 10.1073/pnas.78.10.6201
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of protein glycosylation in the trypanosomatid Crithidia fasciculata.

Abstract: Cells of the insect parasite Crithidia fasciculata incubated with ['4C]glucose were found to possess only one lipidbound oligosaccharide with solubility in chloroform/methanol/ water mixtures and net charge similar to the charges of dolichol pyrophosphate derivatives. The saccharide moiety could be released from lipid by mild acid hydrolysis. Several enzymatic and chemical treatments of the oligosaccharide indicated that the latter had the structure Mana-+Mana---Mana--[Mana-+ Mana-+Man(al--6)]Man--GlcNAc(l1--4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 18 publications
1
36
1
Order By: Relevance
“…The inhibition of radioactivity observed in the lower phase of the chloroform/methanol/water (3:2:1) extract in the tunicamycin experiments suggests the existence of N-linked oligosaccharide intermediates with shorter chains than those found in other glycoproteins [ 17]. Oligosaccharide transferred to proteins in C. fasciculata contained 2 N-acetylglucosamine and only 7 mannose residues [18].…”
Section: Discussionmentioning
confidence: 86%
“…The inhibition of radioactivity observed in the lower phase of the chloroform/methanol/water (3:2:1) extract in the tunicamycin experiments suggests the existence of N-linked oligosaccharide intermediates with shorter chains than those found in other glycoproteins [ 17]. Oligosaccharide transferred to proteins in C. fasciculata contained 2 N-acetylglucosamine and only 7 mannose residues [18].…”
Section: Discussionmentioning
confidence: 86%
“…The mature Dol-PP-oligosaccharide species used for transfer to protein vary according to trypanosomatid species. For example, Trypanosoma conhorini, Trypanosoma dionisii, Leptomonas samueli, Herpetomonas samuelpessoai, and Herpetomonas muscarum utilize triantennary Man 9 GlcNAc 2 -PP-Dol; Crithidia fasciculata, Crithidia harmosa, and Leishmania enriettii utilize biantennary Man 7 GlcNAc 2 -PP-Dol; Leishmania mexicana, Leishmania adleri, and Blastocrithidia culicus utilize biantennary Man 6 GlcNAc 2 -PP-Dol (15)(16)(17)(18). Trypanosoma cruzi, the causative agent of Chagas disease in the Americas, utilizes Man 9 GlcNAc 2 -PP-Dol during most of its life cycle but uses both Man 9 GlcNAc 2 -PP-Dol and Man 7 GlcNAc 2 -PP-Dol in its bloodstream trypomastigote stage (19).…”
mentioning
confidence: 99%
“…14) has shown that protein N-glycosylation in several trypanosomatid parasites is aberrant (15)(16)(17)(18)(19). None of these organisms can make Dol-P-Glc and so fail to make glucosylated Dol-PP-oligosaccharide precursors.…”
mentioning
confidence: 99%
“…The mature dolichol-phosphate-oligosaccharide species used for transfer to protein vary according to trypanosomatid species (17,51,52,56). Therefore, in these organisms, monoglucosylated glycans are exclusively formed through UGGT-dependent glucosylation (12).…”
mentioning
confidence: 99%